A note on phytotoxicity of homodestruxin B – a compound produced by Alternaria brassicae - Bains, P.S.; Tewari, J.P.; Ayer, W.A. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1993)
Homodestruxin B, a compound produced by Alternaria brassicae, the causal organism of the blackspot disease of rapeseed, is known to be phytotoxic to the leaves of Brassica napus. In this study we found that its phytotoxicity was comparable to that of destruxin B, another toxin produced by the pathogen when tested on B. napus. Homodestruxin B caused symptoms of different severities in leaves of various non-host plants. The results suggestthat homodestruxin B is a non-host-specific toxin.